Association Between Medicaid Expansion Under the Affordable Care Act and Survival Among Newly Diagnosed Cancer Patients. (18th May 2022) - Han, Xuesong; Zhao, Jingxuan; Yabroff, K Robin; Johnson, Christopher J; Jemal, Ahmedin
Abstract: Background: Medicaid expansion under the Affordable Care Act (ACA) is associated with increased insurance coverage among patients with cancer. Whether these gains translate to improved survival is largely unknown. This study examines changes in 2-year survival among patients newly diagnosed with cancer following the ACA Medicaid expansion. Methods: Patients aged 18-62 years from 42 states' population-based cancer registries diagnosed pre (2010-2012) and post (2014-2016) ACA Medicaid expansion were followed through September 30, 2013, and December 31, 2017, respectively. Difference-in-differences (DD) analysis of 2-year overall survival was stratified by sex, race and ethnicity, census tract–level poverty, and rurality. Results: A total of 2 555 302 patients diagnosed with cancer were included from Medicaid expansion (n = 1 523 585) and nonexpansion (n = 1 031 717) states. The 2-year overall survival increased from 80.58% pre-ACA to 82.23% post-ACA in expansion states and from 78.71% to 80.04% in nonexpansion states, resulting in a net increase of 0.44 percentage points (ppt) (95% confidence interval [CI] = 0.24ppt to 0.64ppt) in expansion states after adjusting for sociodemographic factors. By cancer site, the net increase was greater for colorectal cancer (DD = 0.90ppt, 95% CI = 0.19ppt to 1.60ppt), lung cancer (DD = 1.29ppt, 95% CI = 0.50ppt to 2.08ppt), non-Hodgkin lymphoma (DD = 1.07ppt, 95% CI = 0.14ppt to 1.99ppt), pancreatic cancer (DD = 1.80ppt, 95% CI = 0.40ppt to 3.21ppt), and liver cancer (DD = 2.57ppt, 95% CI = 1.00ppt to 4.15ppt). The improvement in 2-year overall survival was larger among non-Hispanic Black patients (DD = 0.72ppt, 95% CI = 0.12ppt to 1.31ppt) and patients residing in rural areas (DD = 1.48ppt, 95% CI= -0.26ppt to 3.23ppt), leading to narrowing survival disparities by race and rurality. Conclusions: Medicaid expansion was associated with greater increase in 2-year overall survival, and the increase was prominent among non-Hispanic Blacks and in rural areas, highlighting the role of Medicaid expansion in reducing health disparities. Future studies should monitor changes in longer-term health outcomes following the ACA.